Method for preparing metallic titanium through two-step electrolysis in halide molten salt
By adopting a two-step electrolysis method in the halide molten salt, fluoro-chloride mixed molten salt is used to improve the dissolution capacity and conductivity of TiO2, and electrolytic refining through the molten salt of chloride, the problems of large specific surface area and high energy consumption in the prior art are solved, and the potential of efficient preparation and industrial application of low-oxygen metal titanium is improved.
Patent Information
- Application Number
- CN202411838721.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
The existing methods for preparing metal titanium by electrolysis of molten salts have problems such as large specific surface area, high energy consumption and low efficiency. The dissolution capacity of TiO2 in molten salts of chloride is limited, which limits the potential for industrial applications.
The method of two-step electrolysis in the molten halide salt is adopted. First, the fluoro-chloride mixed molten salt is used to perform primary electrolysis to improve the dissolution capacity and conductivity of TiO2 and reduce the electrolytic temperature; then the molten chloride salt is used for secondary electrolysis refining to obtain low-oxygen metal titanium.
The densification of titanium powder is achieved, the specific surface area and oxygen content is reduced, the current efficiency is improved, the energy consumption is reduced, the electrolysis process is optimized, and the purity and industrial application potential of metal titanium are improved.
Smart Images

Figure HDA0005187433350000011 
Figure HDA0005187433350000012 
Figure HDA0005187433350000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing metallic titanium by two-step electrolysis in halide molten salt, belonging to the technical field of metallurgy. Background Art
[0002] Titanium dioxide has low cost, good chemical stability and high titanium content, and is considered to be an ideal raw material for the industrial electrolytic preparation of titanium metal. The FFC Cambridge method and OS method for electrochemical production of titanium avoid the traditional Kroll method of chlorinating titanium dioxide, refining titanium tetrachloride, electrolytic magnesium production and other processes, greatly reducing production costs, and no chlorine is produced in the process, which will not cause pollution to the environment.
[0003] However, the molten salt electrolysis process of the FFC Cambridge method and the OS method has the disadvantages of low current efficiency and complex production process, which is mainly due to the low solubility of titanium dioxide in pure chloride systems, so it is still very difficult to achieve industrialization. In the existing research on the preparation of titanium metal by molten salt electrolysis of TiO2, chloride-based electrolyte systems have been widely used due to their low electrolysis temperature, high ion migration rate, excellent conductivity and fast mass transfer characteristics. However, the limited solubility of TiO2 in chloride molten salts has become the main bottleneck in its industrial application. In contrast, although the research on fluoride-based electrolyte systems is relatively small, its significant advantage is that TiO2 has a high solubility in fluoride molten salts. However, fluoride molten salts have low conductivity, high electrolysis temperature, and are prone to generate stable fluorine complexes, resulting in a decrease in current efficiency, limiting its potential for widespread application.
[0004] Patent CN113463135B discloses a method for preparing metallic titanium by dissolving and electrolyzing titanium dioxide in fluoride molten salt, using nNaF-K2TiF6 as an electrolyte, titanium dioxide (TiO2) as a soluble titanium source, and graphite or metal as an anode and a metal as a cathode to generate metallic titanium by direct current electrolysis. However, the ionic conductivity of the fluoride molten salt system in this process is relatively weak, resulting in the titanium powder being sponge-like and porous, with a large specific surface area, which in turn results in a high oxygen content in titanium; in addition, in the subsequent impurity removal process, it is difficult to remove impurities with a pure fluoride electrolyte; at the same time, the molten salt temperature is relatively high, resulting in high experimental energy consumption and cost.
[0005] Patent CN113699560B discloses a method for preparing titanium metal by electrolysis of soluble anode in a fluorine-chlorine mixed molten salt system. The method uses TiO2 as raw material to prepare titanium metal, which mainly includes two steps: preparation of highly conductive titanium oxycarbide anode and electrolysis of soluble anode in a fluorine-chlorine mixed system molten salt. High-purity titanium metal products are prepared by adopting special process flows such as secondary fine grinding, secondary briquetting, secondary roasting, pre-electrolysis, and mixed molten salt. However, this method increases the energy consumption of the preparation process of titanium oxycarbide anode and has low production efficiency. Summary of the invention
[0006] In view of the problems of large specific surface area, high energy consumption and low efficiency in the existing molten salt electrolysis for preparing metallic titanium, the present invention proposes a method for preparing metallic titanium by two-step electrolysis in halide molten salt, wherein fluorine-chloride mixed molten salt is used as the primary electrolysis molten salt, fluoride and chloride are combined so that the primary electrolysis molten salt has higher TiO2 solubility capacity and higher conductivity, and the electrolysis temperature of the electrolyte is reduced, the electrolysis process is optimized, the current efficiency is improved, and the energy consumption is reduced; and then chloride molten salt is used as the secondary electrolysis molten salt for electrolytic refining and purification to obtain low-oxygen metallic titanium.
[0007] A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, the specific steps are as follows:
[0008] (1) Using fluorine-chloride mixed molten salt as the primary electrolysis molten salt, adding TiO2 into the fluorine-chloride mixed molten salt and mixing them evenly, heating the fluorine-chloride mixed molten salt containing TiO2 to an electrolysis temperature of 650-850°C under an inert atmosphere, inserting a cathode and an anode, performing a primary molten salt electrolysis, taking out the cathode product, removing impurities from the cathode product by vacuum distillation or washing, and drying to remove the attached electrolyte, thereby obtaining a primary electrolysis product of crude titanium;
[0009] (2) Using the crude titanium produced by the primary electrolysis as a soluble anode, high-purity metallic titanium as a cathode, and chloride molten salt as a secondary electrolysis molten salt, the chloride molten salt is heated to an electrolysis temperature of 550-750°C under an inert atmosphere, and the cathode and anode are inserted for electrolytic refining. The electrolysis product is washed with dilute hydrochloric acid and deionized water to remove impurities and obtain low-oxygen metallic titanium powder.
[0010] Preferably, in the fluoride-chloride mixed molten salt in step (1), the fluoride is K2TiF6 or Na2TiF6, the chloride is one or more of NaCl, KCl, MgCl2, CaCl2, LiCl, the fluoride in the fluoride-chloride mixed molten salt accounts for 40-80wt%, the chloride accounts for 20-60wt%, and the solubility of TiO2 in the fluoride-chloride mixed molten salt is 3-8wt%.
[0011] Preferably, the anode in step (1) is a carbon anode or a metal anode, and the metal anode is a tungsten anode, a molybdenum anode, a Hastelloy anode or a 310S stainless steel anode; the cathode is a titanium cathode, a tungsten cathode, a molybdenum cathode, a stainless steel cathode or a Hastelloy cathode.
[0012] Preferably, the distance between the cathode and the anode in step (1) is 20 to 60 mm, the superheat of the molten salt electrolysis is 30 to 80° C., and the cathode current density of the molten salt electrolysis is greater than the anode current density; more preferably, the cathode current density is 0.6 to 2 A / cm 2 , the anode current density is 0.05~0.5A / cm 2 .
[0013] Preferably, the chloride molten salt in step (2) is one or more of NaCl, KCl, CaCl2, MgCl2, and LiCl.
[0014] Preferably, the distance between the cathode and the anode in step (2) is 30 to 60 mm, and the cathode current density of the electrolytic refining is greater than the anode current density; more preferably, the cathode current density is 0.1 to 1 A / cm 2 , the anode current density is 0.02~0.6A / cm 2 .
[0015] Preferably, the concentration of the dilute hydrochloric acid in step (2) is 1 to 5 wt%.
[0016] The beneficial effects of the present invention are:
[0017] (1) The present invention uses fluorine-chloride mixed molten salt as the primary electrolytic molten salt, combines fluoride with chloride, so that the primary electrolytic molten salt has a higher TiO2 dissolving capacity and higher conductivity, and reduces the electrolysis temperature of the electrolyte, optimizes the electrolysis process, improves the current efficiency, reduces energy consumption, and the obtained titanium powder is dense and has a small specific surface area; then, the chloride molten salt is used as the secondary electrolytic molten salt for electrolytic refining and purification to obtain low-oxygen metallic titanium;
[0018] (2) Both of the two-step electrolysis processes of the present invention adopt a low-melting-point molten salt system, which can effectively reduce energy consumption, ensure the high solubility of TiO2 in the fluorine-chloride mixed molten salt, and ensure that the molten salt system has a high electrical conductivity; the titanium powder obtained by electrolysis of the fluorine-chloride mixed molten salt system has a high density, a small specific surface area and a low oxygen content; after secondary electrolytic refining, the metal titanium powder finally obtained has a lower oxygen content and has a high potential for industrial application;
[0019] (3) The method of the present invention is simple to operate and has a continuous process. The prepared titanium powder has a low oxygen content and has high industrial application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the XRD diagram of the low-oxygen titanium powder of Example 1;
[0021] Figure 2 This is an electron microscope comparison of crude titanium electrolyzed in the fluoride molten salt system of the comparative example and crude titanium electrolyzed in the fluorine-chloride mixed molten salt system of Example 1;
[0022] Figure 3 This is an electron microscope image of crude titanium, a product of the primary electrolysis of Example 2;
[0023] Figure 4 This is an electron microscope image of crude titanium, a product of the primary electrolysis of Example 3;
[0024] Figure 5 This is an electron microscope image of crude titanium, a product of the primary electrolysis of Example 4;
[0025] Figure 6 This is an electron microscope image of crude titanium, a product of the primary electrolysis of Example 5;
[0026] Figure 7 This is an electron microscope image of crude titanium, a product of the primary electrolysis of Example 6;
[0027] Figure 8 This is an electron microscope image of crude titanium, a product of the primary electrolysis of Example 7;
[0028] Fig. 9 This is an electron microscope image of the crude titanium produced by the primary electrolysis in Example 9. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0030] Example 1: A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, the specific steps are as follows:
[0031] (1) Using fluorine-chloride mixed molten salt (80wt% K2TiF6, 10wt% NaCl, 10wt% KCl) as the primary electrolysis molten salt, TiO2 is added to the fluorine-chloride mixed molten salt and mixed evenly (the TiO2 content accounts for 4wt% of the fluorine-chloride mixed molten salt), and under an inert atmosphere (argon), the fluorine-chloride mixed molten salt containing TiO2 is heated to an electrolysis temperature of 720°C, and a cathode (tungsten cathode) and an anode (graphite) are inserted. At a cathode current density of 1.5A / cm 2 , anode current density is 0.17A / cm 2 The molten salt electrolysis was carried out for 8 hours, and the cathode product was taken out. The cathode product was vacuum distilled and washed to remove the attached electrolyte, and dried to obtain the primary electrolysis product crude titanium;
[0032] Taking the fluoride (20wt% NaF, 80wt% K2TiF6) molten salt system as a comparative example, the electron microscope comparison of the crude titanium electrolyzed by the fluoride molten salt system of the comparative example and the crude titanium electrolyzed by the fluorine-chloride mixed molten salt system in Example 1 is shown in Figure 2 , Figure 2 (a) is titanium powder obtained in a fluoride (20wt% NaF, 80wt% K2TiF6) molten salt system, showing a sponge-like and porous morphology; Figure 2 (b) is the titanium powder obtained in the fluoride chloride (80wt% K2TiF6, 10wt% NaCl, 10wt% KCl) molten salt system of this embodiment. Compared with the titanium powder in the fluoride molten salt system, the particle morphology is more compact; this dense structure indicates that the reduction reaction in the fluoride chloride system is more stable and the precipitation process of titanium is more uniform, resulting in an increase in the size of the titanium particles and a denser morphology; this difference indicates that the molten salt system has an important influence on the morphology and particle size of the titanium powder, and the fluoride chloride molten salt system is conducive to the formation of higher density and larger particle size of the titanium powder; in the electrode From the analysis of the electron microscope spectrum, it can be seen that the titanium powder obtained by electrolysis in the fluoride-chloride molten salt system has a relatively dense structure and a low specific surface area; the dense particle structure means that the internal pores of the titanium powder are relatively small, the oxygen content is relatively low, and the precipitation of oxides is limited; therefore, from the electron microscope image, it can be seen that the surface of the titanium powder is smooth and there are no obvious pores in the area, indicating that the electrolysis product is relatively dense, which helps to reduce the adsorption and residue of oxygen, and finally obtains a metal titanium powder with a lower oxygen content; at the same time, this structural feature provides a purer raw material for secondary electrolytic refining, which helps to further improve the purity of metal titanium;
[0033] (2) The primary electrolysis product crude titanium is used as the soluble anode, high-purity metallic titanium is used as the cathode, and the chloride molten salt (50wt% NaCl, 50wt% KCl) is used as the secondary electrolysis molten salt. Under an inert atmosphere (argon), the chloride molten salt is heated to an electrolysis temperature of 700°C, and the cathode and anode are inserted. The cathode current density is 0.6A / cm 2 , anode current density is 0.05A / cm 2 Electrolytic refining was performed for 12 hours under the condition of 400 μm / min, and the electrolytic product was washed with 3 wt% dilute hydrochloric acid, and then repeatedly rinsed with deionized water for 5 times to remove impurities, thereby obtaining low-oxygen titanium metal powder;
[0034] The XRD pattern of the low oxygen titanium powder in this embodiment is shown in Figure 1 According to the characteristic peaks in the spectrum, it can be confirmed that the main phase of the titanium powder is metallic titanium (Ti), and the peak is consistent with the characteristic peak of titanium in the standard card PDF#89-4893; this indicates that the electrolysis process successfully reduced titanium and the crystallinity of titanium is good; Figure 1 No obvious impurity peaks were found in the results, indicating that the obtained titanium powder had a high purity and the by-products produced during the electrolysis process were removed to obtain low-oxygen metal titanium powder.
[0035] The oxygen content in the low-oxygen titanium metal powder of this embodiment is only 0.173%.
[0036] Example 2: A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, the specific steps are as follows:
[0037] (1) A fluorine-chloride mixed molten salt (40 wt% K2TiF6, 30 wt% NaCl, 30 wt% KCl) is used as the primary electrolysis molten salt, TiO2 is added to the fluorine-chloride mixed molten salt and mixed evenly (the TiO2 content accounts for 3 wt% of the fluorine-chloride mixed molten salt), and the fluorine-chloride mixed molten salt containing TiO2 is heated to an electrolysis temperature of 850°C under an inert atmosphere (argon), and a cathode (molybdenum cathode) and an anode (tungsten anode) are inserted. At a cathode current density of 0.8 A / cm 2 , the anode current density is 0.4A / cm 2 The molten salt electrolysis was carried out for 15 hours, and the cathode product was taken out. The cathode product was vacuum distilled and washed to remove the attached electrolyte, and dried to obtain the primary electrolysis product crude titanium;
[0038] The electron microscope image of the crude titanium produced by the primary electrolysis of this embodiment is shown in Figure 3 From the analysis of the electron microscope spectrum, it can be seen that the titanium powder obtained by electrolysis in the fluoride-chloride molten salt system has a relatively dense structure and a low specific surface area; the dense particle structure means that the internal pores of the titanium powder are relatively small, the oxygen content is relatively low, and the precipitation of oxides is limited; therefore, it can be seen from the electron microscope image that the surface of the titanium powder is smooth and there are no obvious pores in the area, indicating that the electrolysis product is relatively dense, which helps to reduce the adsorption and residue of oxygen, and finally obtains a metal titanium powder with a lower oxygen content; at the same time, this structural feature provides a purer raw material for secondary electrolytic refining, which helps to further improve the purity of metal titanium;
[0039] (2) The primary electrolysis product crude titanium is used as the soluble anode, high-purity metallic titanium is used as the cathode, and the chloride molten salt (60wt% NaCl, 40wt% CaCl2) is used as the secondary electrolysis molten salt. Under an inert atmosphere (argon), the chloride molten salt is heated to an electrolysis temperature of 670°C, and the cathode and anode are inserted. The cathode current density is 0.8A / cm 2 , anode current density is 0.10A / cm 2 Electrolytic refining was performed for 15 hours under the condition of 400 μm / min, and the electrolytic product was washed with 5 wt% dilute hydrochloric acid, and then repeatedly rinsed with deionized water for 6 times to remove impurities, thereby obtaining low-oxygen titanium metal powder;
[0040] The oxygen content in the low-oxygen titanium metal powder of this embodiment is only 0.189%.
[0041] Example 3: A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, the specific steps are as follows:
[0042] (1) A fluorine-chloride mixed molten salt (70 wt% K2TiF6, 15 wt% NaCl, 15 wt% CaCl2) is used as the primary electrolysis molten salt, TiO2 is added to the fluorine-chloride mixed molten salt and mixed evenly (the TiO2 content accounts for 4 wt% of the fluorine-chloride mixed molten salt), and the fluorine-chloride mixed molten salt containing TiO2 is heated to an electrolysis temperature of 800°C under an inert atmosphere (argon), and a cathode (molybdenum cathode) and an anode (tungsten anode) are inserted. At a cathode current density of 1.2 A / cm 2 , the anode current density is 0.4A / cm 2 The molten salt electrolysis was carried out for 5 hours, and the cathode product was taken out. The cathode product was vacuum distilled and washed to remove the attached electrolyte, and dried to obtain the primary electrolysis product crude titanium;
[0043] The electron microscope image of the crude titanium produced by the primary electrolysis of this embodiment is shown in Figure 4 From the analysis of the electron microscope spectrum, it can be seen that the titanium powder obtained by electrolysis in the fluoride-chloride molten salt system has a relatively dense structure and a low specific surface area; the dense particle structure means that the internal pores of the titanium powder are relatively small, the oxygen content is relatively low, and the precipitation of oxides is limited; therefore, it can be seen from the electron microscope image that the surface of the titanium powder is smooth and there are no obvious pores in the area, indicating that the electrolysis product is relatively dense, which helps to reduce the adsorption and residue of oxygen, and finally obtains a metal titanium powder with a lower oxygen content; at the same time, this structural feature provides a purer raw material for secondary electrolytic refining, which helps to further improve the purity of metal titanium;
[0044] (2) The primary electrolysis product crude titanium is used as the soluble anode, high-purity metallic titanium is used as the cathode, and the chloride molten salt (50wt% KCl, 50wt% LiCl) is used as the secondary electrolysis molten salt. Under an inert atmosphere (argon), the chloride molten salt is heated to an electrolysis temperature of 550°C, and the cathode and anode are inserted. The cathode current density is 1A / cm 2 , anode current density is 0.15A / cm 2 Electrolytic refining was performed for 16 hours under the condition of 400 μm / min, and the electrolytic product was washed with 1 wt% dilute hydrochloric acid, and then repeatedly rinsed with deionized water for 5 times to remove impurities, thereby obtaining low-oxygen titanium metal powder;
[0045] The oxygen content in the low-oxygen titanium metal powder of this embodiment is only 0.162%.
[0046] Example 4: A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, the specific steps are as follows:
[0047] (1) A fluorine-chloride mixed molten salt (70 wt% Na2TiF6, 15 wt% NaCl, 15 wt% CaCl2) is used as the primary electrolysis molten salt, TiO2 is added to the fluorine-chloride mixed molten salt and mixed evenly (the TiO2 content accounts for 5 wt% of the fluorine-chloride mixed molten salt), and the fluorine-chloride mixed molten salt containing TiO2 is heated to an electrolysis temperature of 820°C under an inert atmosphere (argon), and a cathode (titanium cathode) and an anode (tungsten anode) are inserted. At a cathode current density of 1.5 A / cm 2 , anode current density is 0.25A / cm 2 The molten salt electrolysis was carried out for 6 hours, and the cathode product was taken out. The cathode product was vacuum distilled and washed to remove the attached electrolyte, and dried to obtain the primary electrolysis product crude titanium;
[0048] The electron microscope image of the crude titanium produced by the primary electrolysis of this embodiment is shown in Figure 5 From the analysis of the electron microscope spectrum, it can be seen that the titanium powder obtained by electrolysis in the fluoride-chloride molten salt system has a relatively dense structure and a low specific surface area; the dense particle structure means that the internal pores of the titanium powder are relatively small, the oxygen content is relatively low, and the precipitation of oxides is limited; therefore, it can be seen from the electron microscope image that the surface of the titanium powder is smooth and there are no obvious pores in the area, indicating that the electrolysis product is relatively dense, which helps to reduce the adsorption and residue of oxygen, and finally obtains a metal titanium powder with a lower oxygen content; at the same time, this structural feature provides a purer raw material for secondary electrolytic refining, which helps to further improve the purity of metal titanium;
[0049] (2) The primary electrolysis product crude titanium is used as the soluble anode, high-purity metallic titanium is used as the cathode, and the chloride molten salt (30wt% MgCl2, 70wt% LiCl) is used as the secondary electrolysis molten salt. Under an inert atmosphere (argon), the chloride molten salt is heated to an electrolysis temperature of 550°C, and the cathode and anode are inserted. The cathode current density is 0.7A / cm 2 , anode current density is 0.3A / cm 2 Electrolytic refining was performed for 24 hours, and the electrolytic product was washed with 2 wt% dilute hydrochloric acid, and then repeatedly rinsed with deionized water for 5 times to remove impurities, thereby obtaining low-oxygen titanium metal powder;
[0050] The oxygen content in the low-oxygen titanium metal powder of this embodiment is only 0.146%.
[0051] Example 5: A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, the specific steps are as follows:
[0052] (1) A fluorine-chloride mixed molten salt (60 wt% K2TiF6, 20 wt% NaCl, 20 wt% KCl) is used as the primary electrolysis molten salt, TiO2 is added to the fluorine-chloride mixed molten salt and mixed evenly (the TiO2 content accounts for 3 wt% of the fluorine-chloride mixed molten salt), and the fluorine-chloride mixed molten salt containing TiO2 is heated to an electrolysis temperature of 780°C under an inert atmosphere (helium), and a cathode (titanium cathode) and an anode (graphite anode) are inserted. At a cathode current density of 1 A / cm 2 , the anode current density is 0.2A / cm 2 The molten salt electrolysis was carried out for 3 hours, and the cathode product was taken out. The cathode product was vacuum distilled and washed to remove the attached electrolyte, and dried to obtain the primary electrolysis product crude titanium;
[0053] The electron microscope image of the crude titanium produced by the primary electrolysis of this embodiment is shown in Figure 6 From the analysis of the electron microscope spectrum, it can be seen that the titanium powder obtained by electrolysis in the fluoride-chloride molten salt system has a relatively dense structure and a low specific surface area; the dense particle structure means that the internal pores of the titanium powder are relatively small, the oxygen content is relatively low, and the precipitation of oxides is limited; therefore, it can be seen from the electron microscope image that the surface of the titanium powder is smooth and there are no obvious pores in the area, indicating that the electrolysis product is relatively dense, which helps to reduce the adsorption and residue of oxygen, and finally obtains a metal titanium powder with a lower oxygen content; at the same time, this structural feature provides a purer raw material for secondary electrolytic refining, which helps to further improve the purity of metal titanium;
[0054] (2) The primary electrolysis product crude titanium is used as the soluble anode, high-purity metallic titanium is used as the cathode, and the chloride molten salt (40wt% CaCl, 60wt% KCl) is used as the secondary electrolysis molten salt. Under an inert atmosphere (argon), the chloride molten salt is heated to an electrolysis temperature of 650°C, and the cathode and anode are inserted. The cathode current density is 0.1A / cm 2 , anode current density is 0.02A / cm 2 Electrolytic refining was performed for 20 hours, the electrolytic product was washed with 5 wt% dilute hydrochloric acid, and then repeatedly rinsed with deionized water for 5 times to remove impurities, thereby obtaining low-oxygen titanium metal powder;
[0055] The oxygen content in the low-oxygen titanium powder of this embodiment is only 0.086%.
[0056] Example 6: A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, the specific steps are as follows:
[0057] (1) A fluorine-chloride mixed molten salt (40 wt% Na2TiF6, 30 wt% NaCl, 30 wt% KCl) is used as the primary electrolysis molten salt, TiO2 is added to the fluorine-chloride mixed molten salt and mixed evenly (the TiO2 content accounts for 6 wt% of the fluorine-chloride mixed molten salt), and the fluorine-chloride mixed molten salt containing TiO2 is heated to an electrolysis temperature of 650°C under an inert atmosphere (helium), and a cathode (Hastelloy cathode) and an anode (graphite anode) are inserted. At a cathode current density of 1.5 A / cm 2 , anode current density is 0.25A / cm 2 The molten salt electrolysis was carried out for 10 hours, and the cathode product was taken out. The cathode product was vacuum distilled and washed to remove the attached electrolyte, and dried to obtain the primary electrolysis product crude titanium;
[0058] The electron microscope image of the crude titanium produced by the primary electrolysis of this embodiment is shown in Figure 7 From the analysis of the electron microscope spectrum, it can be seen that the titanium powder obtained by electrolysis in the fluoride-chloride molten salt system has a relatively dense structure and a low specific surface area; the dense particle structure means that the internal pores of the titanium powder are relatively small, the oxygen content is relatively low, and the precipitation of oxides is limited; therefore, it can be seen from the electron microscope image that the surface of the titanium powder is smooth and there are no obvious pores in the area, indicating that the electrolysis product is relatively dense, which helps to reduce the adsorption and residue of oxygen, and finally obtains a metal titanium powder with a lower oxygen content; at the same time, this structural feature provides a purer raw material for secondary electrolytic refining, which helps to further improve the purity of metal titanium;
[0059] (2) The primary electrolysis product crude titanium is used as the soluble anode, high-purity metallic titanium is used as the cathode, and the chloride molten salt (45wt% NaCl, 55wt% KCl) is used as the secondary electrolysis molten salt. Under an inert atmosphere (argon), the chloride molten salt is heated to an electrolysis temperature of 680°C, and the cathode and anode are inserted. The cathode current density is 1A / cm 2 , the anode current density is 0.5A / cm 2 Electrolytic refining was performed for 28 hours, and the electrolytic product was washed with 4 wt% dilute hydrochloric acid, and then repeatedly rinsed with deionized water for 5 times to remove impurities, thereby obtaining low-oxygen titanium metal powder;
[0060] The oxygen content in the low-oxygen titanium powder of this embodiment is only 0.126%.
[0061] Example 7: A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, the specific steps are as follows:
[0062] (1) A fluorine-chloride mixed molten salt (80 wt% Na2TiF6, 10 wt% NaCl, 10 wt% KCl) is used as the primary electrolysis molten salt, TiO2 is added to the fluorine-chloride mixed molten salt and mixed evenly (the TiO2 content accounts for 8 wt% of the fluorine-chloride mixed molten salt), and the fluorine-chloride mixed molten salt containing TiO2 is heated to an electrolysis temperature of 850°C under an inert atmosphere (argon), and a cathode (tungsten cathode) and an anode (graphite anode) are inserted. At a cathode current density of 0.7 A / cm 2 , anode current density is 0.3A / cm 2 A molten salt electrolysis was performed for 9 hours, and the cathode product was taken out. The cathode product was vacuum distilled and washed to remove the attached electrolyte, and dried to obtain the primary electrolysis product crude titanium;
[0063] The electron microscope image of the crude titanium produced by the primary electrolysis of this embodiment is shown in Figure 8 From the analysis of the electron microscope spectrum, it can be seen that the titanium powder obtained by electrolysis in the fluoride-chloride molten salt system has a relatively dense structure and a low specific surface area; the dense particle structure means that the internal pores of the titanium powder are relatively small, the oxygen content is relatively low, and the precipitation of oxides is limited; therefore, it can be seen from the electron microscope image that the surface of the titanium powder is smooth and there are no obvious pores in the area, indicating that the electrolysis product is relatively dense, which helps to reduce the adsorption and residue of oxygen, and finally obtains a metal titanium powder with a lower oxygen content; at the same time, this structural feature provides a purer raw material for secondary electrolytic refining, which helps to further improve the purity of metal titanium;
[0064] (2) The primary electrolysis product crude titanium is used as the soluble anode, high-purity metallic titanium is used as the cathode, and the chloride molten salt (70wt% NaCl, 30wt% LiCl) is used as the secondary electrolysis molten salt. Under an inert atmosphere (argon), the chloride molten salt is heated to an electrolysis temperature of 750°C, and the cathode and anode are inserted. The cathode current density is 0.5A / cm 2 , the anode current density is 0.2A / cm 2 Electrolytic refining was performed for 25 hours, and the electrolytic product was washed with 2 wt% dilute hydrochloric acid, and then repeatedly rinsed with deionized water for 5 times to remove impurities, thereby obtaining low-oxygen titanium metal powder;
[0065] The oxygen content in the low-oxygen titanium metal powder of this embodiment is only 0.153%.
[0066] Example 8: A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, the specific steps are as follows:
[0067] (1) A fluorine-chloride mixed molten salt (60 wt% K2TiF6, 20 wt% NaCl, 20 wt% CaCl) is used as the primary electrolysis molten salt, TiO2 is added to the fluorine-chloride mixed molten salt and mixed evenly (the TiO2 content accounts for 3 wt% of the fluorine-chloride mixed molten salt), and the fluorine-chloride mixed molten salt containing TiO2 is heated to an electrolysis temperature of 750°C under an inert atmosphere (argon), and a cathode (molybdenum cathode) and an anode (graphite anode) are inserted. At a cathode current density of 2 A / cm 2 , the anode current density is 0.5A / cm 2 The molten salt electrolysis was carried out for 10 hours, and the cathode product was taken out. The cathode product was vacuum distilled and washed to remove the attached electrolyte, and dried to obtain the primary electrolysis product crude titanium;
[0068] The electron microscope image of the crude titanium produced by the primary electrolysis of this embodiment is shown in Fig. 9 From the analysis of the electron microscope spectrum, it can be seen that the titanium powder obtained by electrolysis in the fluoride-chloride molten salt system has a relatively dense structure and a low specific surface area; the dense particle structure means that the internal pores of the titanium powder are relatively small, the oxygen content is relatively low, and the precipitation of oxides is limited; therefore, it can be seen from the electron microscope image that the surface of the titanium powder is smooth and there are no obvious pores in the area, indicating that the electrolysis product is relatively dense, which helps to reduce the adsorption and residue of oxygen, and finally obtains a metal titanium powder with a lower oxygen content; at the same time, this structural feature provides a purer raw material for secondary electrolytic refining, which helps to further improve the purity of metal titanium;
[0069] (2) The primary electrolysis product crude titanium is used as the soluble anode, high-purity metallic titanium is used as the cathode, and the chloride molten salt (50wt% NaCl, 50wt% MgCl2) is used as the secondary electrolysis molten salt. Under an inert atmosphere (argon), the chloride molten salt is heated to the electrolysis temperature of 700°C, and the cathode and anode are inserted. The cathode current density is 0.7A / cm 2 , anode current density is 0.18A / cm 2 Electrolytic refining was performed for 36 hours, and the electrolytic product was washed with 2 wt% dilute hydrochloric acid, and then repeatedly rinsed with deionized water for 5 times to remove impurities, thereby obtaining low-oxygen titanium metal powder;
[0070] The oxygen content in the low-oxygen titanium metal powder of this embodiment is only 0.181%.
[0071] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing metallic titanium by two-step electrolysis in a halide molten salt, characterized in that: The specific steps are as follows: (1) Using fluorine-chloride mixed molten salt as the primary electrolysis molten salt, adding TiO2 into the fluorine-chloride mixed molten salt and mixing them evenly, heating the fluorine-chloride mixed molten salt containing TiO2 to an electrolysis temperature of 650-850°C under an inert atmosphere, inserting a cathode and an anode, performing a primary molten salt electrolysis, taking out the cathode product, removing impurities from the cathode product by vacuum distillation or washing, and drying to remove the attached electrolyte, thereby obtaining a primary electrolysis product of crude titanium; (2) Using the crude titanium produced by the primary electrolysis as a soluble anode, high-purity metallic titanium as a cathode, and chloride molten salt as a secondary electrolysis molten salt, the chloride molten salt is heated to an electrolysis temperature of 550-750°C under an inert atmosphere, and the cathode and anode are inserted for electrolytic refining. The electrolysis product is washed with dilute hydrochloric acid and deionized water to remove impurities and obtain low-oxygen metallic titanium powder.
2. The method for preparing metallic titanium by two-step electrolysis in a halide molten salt according to claim 1, characterized in that: In step (1), the fluoride in the fluorine-chloride mixed molten salt is K2TiF6 or Na2TiF6, the chloride is one or more of NaCl, KCl, MgCl2, CaCl2, and LiCl, the fluoride in the fluorine-chloride mixed molten salt accounts for 40 to 80 wt%, the chloride accounts for 20 to 60 wt%, and the solubility of TiO2 in the fluorine-chloride mixed molten salt is 3 to 8 wt%.
3. The method for preparing metallic titanium by two-step electrolysis in a halide molten salt according to claim 1, characterized in that: In step (1), the anode is a carbon anode or a metal anode, and the metal anode is a tungsten anode, a molybdenum anode, a Hastelloy anode or a 310S stainless steel anode; the cathode is a titanium cathode, a tungsten cathode, a molybdenum cathode, a stainless steel cathode or a Hastelloy cathode.
4. The method for preparing metallic titanium by two-step electrolysis in a halide molten salt according to claim 1, characterized in that: Step (1) The distance between the cathode and the anode is 20 to 60 mm, the superheat of the primary molten salt electrolysis is 30 to 80°C, and the cathode current density is 0.6 to 2 A / cm 2 , the anode current density is 0.05~0.5A / cm 2 .
5. The method for preparing metallic titanium by two-step electrolysis in a halide molten salt according to claim 1, characterized in that: The chloride molten salt in step (2) is one or more of NaCl, KCl, CaCl2, MgCl2, and LiCl.
6. The method for preparing metallic titanium by two-step electrolysis in a halide molten salt according to claim 1, characterized in that: Step (2) The distance between the cathode and the anode is 30 to 60 mm, and the cathode current density of the electrolytic refining is 0.1 to 1 A / cm 2 , the anode current density is 0.02~0.6A / cm 2 .
7. The method for preparing metallic titanium by two-step electrolysis in a halide molten salt according to claim 1, characterized in that: The concentration of the dilute hydrochloric acid in step (2) is 1 to 5 wt%.
Citation Information
Patent Citations
A method for preparing metallic titanium by dissolving and electrolyzing titanium dioxide in fluoride molten salt
CN113463135B
A method for preparing metallic titanium by soluble anodic electrolysis in a fluorine-chlorine mixed molten salt system
CN113699560B
Cited By
Resource recycling treatment method for waste incineration fly ash
CN121551361A